2015
DOI: 10.1080/07481187.2015.1047061
|View full text |Cite
|
Sign up to set email alerts
|

Physical Disability and the Interpersonal Theory of Suicide

Abstract: Interpersonal Theory of Suicide constructs were examined in individuals with physical disabilities, a population identified as having heightened suicidal ideation. Students (N = 184) answered online-based self-report questionnaires. Students with physical disabilities (n = 49) were expected to endorse higher levels of constructs relative to other students (n = 133). Analyses of covariance indicated that those with disabilities reported higher perceived burdensomeness, but not thwarted belongingness, fearlessne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…According to the ITS, suicidal ideation is most likely to occur in the joint presence of perceived burdensomeness, the belief that one is a burden to others to the extent that they would benefit from the individuals' death, and thwarted belongingness, a belief of a lack of meaningful connection to others. Although heightened perceived burdensomeness has been observed in those who endorsed having physical disabilities (Khazem, Jahn, Cukrowicz, & Anestis, ), physical disability was not indirectly associated with suicidal ideation through perceived burdensomeness (Khazem et al, ; Khazem, Jahn, Cukrowicz, & Anestis, ). Furthermore, findings from the limited research examining the contribution of thwarted belongingness to suicidal ideation in this population are also mixed (Khazem et al, ; Wilson, Kowal, Henderson, McWilliams, & Péloquin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ITS, suicidal ideation is most likely to occur in the joint presence of perceived burdensomeness, the belief that one is a burden to others to the extent that they would benefit from the individuals' death, and thwarted belongingness, a belief of a lack of meaningful connection to others. Although heightened perceived burdensomeness has been observed in those who endorsed having physical disabilities (Khazem, Jahn, Cukrowicz, & Anestis, ), physical disability was not indirectly associated with suicidal ideation through perceived burdensomeness (Khazem et al, ; Khazem, Jahn, Cukrowicz, & Anestis, ). Furthermore, findings from the limited research examining the contribution of thwarted belongingness to suicidal ideation in this population are also mixed (Khazem et al, ; Wilson, Kowal, Henderson, McWilliams, & Péloquin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although heightened perceived burdensomeness has been observed in those who endorsed having physical disabilities (Khazem, Jahn, Cukrowicz, & Anestis, ), physical disability was not indirectly associated with suicidal ideation through perceived burdensomeness (Khazem et al, ; Khazem, Jahn, Cukrowicz, & Anestis, ). Furthermore, findings from the limited research examining the contribution of thwarted belongingness to suicidal ideation in this population are also mixed (Khazem et al, ; Wilson, Kowal, Henderson, McWilliams, & Péloquin, ). Given these findings, the possibility exists that physical disability may contribute to the development of suicidal ideation independent of the influence of these states.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified higher perceived burdensomeness among those with physical disabilities (Khazem, Jahn, Cukrowicz, & Anestis, 2015) and older adults (Cukrowicz, Cheavens, van Orden, Ragain, & Cook, 2011), which suggests a need for tailored treatment for such individuals. CT-SP is well-positioned to explicitly address cognitive distortions that arise within the domain of perceived burdensomeness, and thus may be especially effective for military personnel who experience suicidal thoughts in this context.…”
mentioning
confidence: 99%
“…In this way, CT-SP may not be sufficient as an intervention, as the burdensomeness is not merely perceived. Previous research has identified higher perceived burdensomeness among those with physical disabilities (Khazem, Jahn, Cukrowicz, & Anestis, 2015) and older adults (Cukrowicz, Cheavens, van Orden, Ragain, & Cook, 2011), which suggests a need for tailored treatment for such individuals. Additionally, those bullied due to sexual orientation or race are members of socially vulnerable groups that are susceptible to higher rates of bullying and may require programs specifically directed towards eliminating the bullying of minority groups (Llorent, Ortega & Zych, 2016).…”
mentioning
confidence: 99%
“…Evidence suggests, for instance, that greater medical comorbidity and functional disability may exacerbate geriatric depression, hindering treatment progress and slowing symptom remission (Alexopoulos et al , 1999; Szanto et al , 2003; Alexopoulos, 2005). Likewise, perceived burdensomeness, which may result from illness and functional disability (Khazem et al , 2015), increases risk of SI (Cukrowicz et al , 2011; Hill and Pettit, 2014; Guidry and Cukrowicz, 2015); however there are few studies exploring the influence of perceived burdensomeness on longitudinal course of SI (Hill and Pettit, 2014). While medical comorbidity, functional disabilities, and perceived burdensomeness are established risk factors for SI, it is unclear to what extent these factors may influence remission or persistence among depressed HHC patients.…”
Section: Introductionmentioning
confidence: 99%